2004
DOI: 10.1083/jcb.200402016
|View full text |Cite
|
Sign up to set email alerts
|

Differential transactivation of sphingosine-1-phosphate receptors modulates NGF-induced neurite extension

Abstract: The process of neurite extension after activation of the TrkA tyrosine kinase receptor by nerve growth factor (NGF) involves complex signaling pathways. Stimulation of sphingosine kinase 1 (SphK1), the enzyme that phosphorylates sphingosine to form sphingosine-1-phosphate (S1P), is part of the functional TrkA signaling repertoire. In this paper, we report that in PC12 cells and dorsal root ganglion neurons, NGF translocates SphK1 to the plasma membrane and differentially activates the S1P receptors S1P1 and S1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(170 citation statements)
references
References 45 publications
7
162
1
Order By: Relevance
“…Neurite initiation and formation involve actin cytoskeletal changes, and as a regulator of actin reorganization, Rho GTPase has a profound effect on neuritogenesis (47). For example, S1P induces Rho-dependent neurite retraction through the S1P 2 (49,50), S1P 3 (49), and S1P 5 receptors (50,51). Several studies have also revealed a critical role for Rho and ROCK in LPA-induced neurite retraction (36,52,53), although some studies have reported Rhoindependent neurite retraction (38,54).…”
Section: Discussionmentioning
confidence: 99%
“…Neurite initiation and formation involve actin cytoskeletal changes, and as a regulator of actin reorganization, Rho GTPase has a profound effect on neuritogenesis (47). For example, S1P induces Rho-dependent neurite retraction through the S1P 2 (49,50), S1P 3 (49), and S1P 5 receptors (50,51). Several studies have also revealed a critical role for Rho and ROCK in LPA-induced neurite retraction (36,52,53), although some studies have reported Rhoindependent neurite retraction (38,54).…”
Section: Discussionmentioning
confidence: 99%
“…by guest, on September 1, 2018 www.jlr.org Downloaded from translocation to the plasma membrane ( 73,74 ) where its substrate, Sph, is found ( 70 ). SphK1 is responsible for S1P-mitogenic and anti-apoptotic effects; its exogenous expression induces cell proliferation and pro-survival signals whereas its downregulation activates proapoptotic events ( 75 ).…”
Section: The Sphingolipids: a Vast Familymentioning
confidence: 99%
“…Information on the clues required for controlling its proliferation and further differentiation into photoreceptors is a prerequisite to take advantage of these cells for this regenerative purpose. S1P is involved in neuritogenesis, promoting either neurite extension or retraction, depending on the type of activated S1P receptor ( 69,73,208 ). In Xenopus retina, it participates in controlling axonal outgrowth, eliciting repulsive responses in growth cones ( 69 ).…”
Section: Sphingosine In the Retinamentioning
confidence: 99%
“…This is very similar to K Na reported in Xenopus spinal neurons (Dale, 1993), lamprey spinal cord neurons (Hess et al, 2007), and rat olfactory neurons (Budelli et al, 2009). These cultured embryonic neurons are ideal because they are also homogenous in their firing properties (Chen et al, 1987;Grigaliunas et al, 2002;Toman et al, 2004). Neurons are cultured in serum-free medium containing NGF.…”
Section: Cultured Drg Neurons Contain Slack K Na Channelsmentioning
confidence: 99%